Fumarase From Cyanidioschyzon merolae Stably Shows High Catalytic Activity for Fumarate Hydration Under High Temperature Conditions - Ito, Shoki; Iwazumi, Kaori; Sukigara, Haruna; Osanai, Takashi (Frontiers in Microbiology, 2020)
Fumarases (Fums) catalyze the reversible reaction converting fumarate to l-malate. There are two kinds of Fums: Class І and ІІ. Thermostable Class ІІ Fums, from mesophilic microorganisms, are utilized for industrial l-malate production. However, the low thermostability of these Fums is a limitation in industrial l-malate production. Therefore, an alternative Class ІІ Fum that shows high activity and thermostability is required to overcome this drawback. Thermophilic microalgae and cyanobacteria can use carbon dioxide as a carbon source and are easy to cultivate. Among them, Cyanidioschyzon merolae and Thermosynechococcus elongatus are model organisms to study cell biology and structural biology, respectively. We biochemically analyzed Class ІІ Fums from C. merolae (CmFUM) and T. elongatus (TeFum). Both CmFUM and TeFum preferentially catalyzed fumarate hydration. The catalytic activity of CmFUM for fumarate hydration in the optimum conditions (52°C and pH 7.5) is higher compared to those of Class ІІ Fums from other organisms and TeFum. Thermostability tests of CmFUM revealed that CmFUM showed higher thermostability than those of Class ІІ Fums from other microorganisms. The yield of l-malate obtained from fumarate hydration catalyzed by CmFUM was 75–81%. In summary, CmFum has suitable properties for efficient l-malate production.